Body Mass Index Trajectories in the First 5 Years and Associated Antenatal Factors - Mattsson, Molly; Murray, Deirdre M.; Hawkes, Colin P.; Kiely, Mairead; Ní Chaoimh, Carol; McCarthy, Fergus P.; Biesma, Regien; Boland, Fiona (Frontiers in Pediatrics, 2021)
Abstract Background The increasing prevalence of childhood obesity is an important public health issue and the development of obesity in early life and associated risk factors need to be better understood. The aim of this study was to identify distinct body mass index trajectories in the first five years of life and to examine their associations with factors identified in pregnancy, including metabolic parameters. Methods BMI measurements from 2,172 children in Ireland enrolled in the BASELINE cohort study with BMI assessments at birth, 2, 6, and 12 months, and 2 and 5 years were analysed. Growth mixture modelling was used to identify distinct BMI trajectories, and multivariate multinomial logistic regression was used to assess the association between these trajectories and antenatal factors. Results Three distinct BMI trajectories were identified: normal (89.6%); rapid gain in the first 6 months (7.8%); and rapid BMI after 12 months (2.6%). Male sex and higher maternal age increased the likelihood of belonging to the rapid gain in the first 6 months trajectory. Raised maternal BMI at 15 weeks of pregnancy and lower cord blood IGF-2 were associated with rapid gain after 1 year. Conclusion Sex, maternal age and BMI, and IGF-2 levels were found to be associated with BMI trajectories in early childhood departing from normal growth. Further research and extended follow-up to examine the effects of childhood growth patterns are required to understand their relationship with health outcomes.